Coating combustion synthesis controlled by moving electron beam; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects". 3rd International Conference on New Materials and High Technologies (3rd NMHT) - Knyazeva A. G. Anna Georgievna (2018, 2018)
Title screen